2017
DOI: 10.1186/s13584-017-0185-9
|View full text |Cite
|
Sign up to set email alerts
|

Applying a community-based participatory research approach to improve access to healthcare for Eritrean asylum-seekers in Israel: a pilot study

Abstract: BackgroundIsrael hosts approximately 50,000 asylum seekers, most of them from Eritrea. Exclusive policies restrict their access to healthcare. In 2013, local activists partnered with Eritrean asylum seekers to assess health needs as well as willingness to pay for health insurance among the Eritrean communities. This initiative was meant as a step towards jointly advocating access to Israel’s public healthcare system and towards strengthening collective efficacy among the asylum-seeking communities, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…Several studies show that refugees do make use of healthcare services in host countries, although their usage is characterized as "limited" (Carolan, 2010), "underutilized" (Choi et al, 2015), "restricted" (Gottlieb et al, 2017;Langlois et al, 2016) or "low" (Correa-Velez and Ryan, 2012), especially compared to citizens' use of these services in the host country. Studies that analyze the underlying mechanisms of such user rates tend to focus on visible, measurable factors, such as availability (e.g.…”
Section: Preliminary Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies show that refugees do make use of healthcare services in host countries, although their usage is characterized as "limited" (Carolan, 2010), "underutilized" (Choi et al, 2015), "restricted" (Gottlieb et al, 2017;Langlois et al, 2016) or "low" (Correa-Velez and Ryan, 2012), especially compared to citizens' use of these services in the host country. Studies that analyze the underlying mechanisms of such user rates tend to focus on visible, measurable factors, such as availability (e.g.…”
Section: Preliminary Studymentioning
confidence: 99%
“…In theory, the abovementioned services are available to all in Israel, citizens and refugees alike. However, in practice, not all Eritrean refugees have health coverage, although exact numbers are unknown (Gottlieb et al, 2017). For uninsured migrants, the Terem Clinic, run by the Israeli Medical Association with help from the Ministry of Health, offers basic pregnancy services.…”
Section: The Contextmentioning
confidence: 99%
“…In an article recently published in the IJHPR, Gottlieb et al [ 4 ] reported the results of the first attempt to apply a community-based participatory research (CBPR) approach to migrant health research in Israel [ 4 ]. That pilot study was conducted among Eritrean asylum seekers in four Israeli cities.…”
Section: Commentarymentioning
confidence: 99%
“…Meta‐reviews have concluded that such utilization is “limited” and “late” (Carolan, : 411), “low” (Correa‐Velez and Ryan, : 14) and “less” and “later” than user rates of host country citizens (e.g., Munro et al., : 283). Numerous case studies also point to refugees’ problematic or low utilization of health services (e.g., Asgary and Segar, ; Correa‐Velez and Ryan, ; Michaan et al., ; Choi et al., ; Langlois et al., ; Gottlieb et al., ), although a few studies argue that there is “no evidence of under‐use” (Kiss et al., : 57), that access for refugees is “relatively good” (El Arab and Sagbakken, ), and that refugees’ demands for health services are “largely met” (Borgschulte et al., : 6). The findings of both positive and negative health service utilization in host countries begs the question of how such use is conceptualized and operationalized, as well as how it is contextualized, that is, what country‐specific legislation relates to refugees and their entitlement to health services in the host country.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, Gottlieb et al. () contend that Eritrean refugees in Israel are willing to obtain health insurance and place great value on health services, suggesting that their general lack of health insurance in Israel is the result of structural constraints rather than personal preference. Taken as a whole, these studies suggest that Israel is a problematic context for refugee health service utilization in terms of both legislation and practice.…”
Section: Introductionmentioning
confidence: 99%